The fall of the house of West - Petty, J. T. (John T.); Pope, Paul (First Second, 2015)
Trying to track her mother's killer in secret hasn't been easy for Aurora West, but when her father finally agrees that she's old enough to go on patrol alone, she finds the perfect opportunity to put her plan to avenger her mom's death into action. But doing so could put all of Arcopolis in danger.